Strategi Sekretaris Desa Dalam Meningkatkan Kualitas Layanan Administrasi di Desa Bakah Kecamatan Kunduran Kabupaten Blora - Rozani, Ahmad; Oktarina, Nina (Universitas Negeri Semarang, 2025)
This study explores the role of the village secretary in improving the quality of administrative services in Bakah Village, Kunduran Sub-district, Blora Regency. Using a qualitative approach and thematic analysis techniques, data was collected through interviews, observation, and documentation. The findings show that the village secretary is responsible for designing development plans and managing village data, but is often faced with additional tasks that interfere with the main focus. One of the strategies implemented is the digitization of Bakah Village Book C into a digital map to facilitate access to land information. Other strategies include developing information technology competencies, increasing human resource capacity and collaborating with village officials. Despite obstacles such as limited resources and resistance to change, this study recommends additional staff, technology training, and the development of standard operating procedures (SOPs) to improve service effectiveness. The results are expected to provide insights for the development of public service policies at the village level.